Implementing the PJBL (Project Based Learning) Method Using Canva Infographics to Improve Student’s Creativity and Multicultural Understanding - Purnamasari, Dyah Emarikhatul (IJTIMAIYA: Journal of Social Science and Teaching, 2023)
The low level of creativity and the understanding of students in the process of learning sociology a problem we are very classical at school. This research has the aims to describe the implementation of the Canva Infographic-based on PjBL (Project Based Learning) method in terms of increasing students' understanding and creativity. This type of research is descriptive qualitative. Data collection techniques used are interviews and documentation. The type of data used is primary and secondary data. The results of this research are that through the Canva Infographic-based PjBL method, students become more active and creative in the learning process because students are a source of learning. Students search for the material to be studied themselves then present and discuss the results of the PjBL that have been done. Students creativity are based on the creativity of students infographics, the originality of the project and the smoothness and flexibility of the presentation and discussion process. The process of learning this project consists of several stages of the student learning process, namely collecting information, doing projects, presenting and discussing. Based on these stages, the PjBL method learning process was successful in increasing students' understanding and creativity.